Perilaku Politik Pemilih di Desa Ciptamargi Kecamatan Cilebar Kabupaten Karawang pada Pilkada 2020 Studi Kasus di TPS 02 Desa Ciptamargi - Sandra Mutiara Pratiwi; Hanny Purnamasari; Prilla Marsingga (Peneliti.net, 2022)
This study tries to bring to the surface related to the emergence of interesting phenomena in the political behavior of the people in Ciptamargi Village, Cilebar District, Karawang Regency. In this study, the author uses the theory According to Dennis Kavanagh which says that the political behavior of voters can be analyzed with 3 (five) approaches, namely: sociological, psychological and rationalist approaches. In general, the political behavior of voters that can be illustrated in this study is that most of the people still tend to be realistic and adhere to a political flow that prioritizes regionalism. Some other people also choose candidates based on their figures. In addition to those previously mentioned, rural communities will choose candidates because of the candidate's proximity to the community and other rational reasons, such as money politics. This is of course reasonable to happen, because the theory of social exchange states that social interaction in various structures of society will occur if there is exchange of activities, in the form of material or non-material